L’enseignement/Apprentissage De L’expression Orale Au Lyceée : Les Problèmes Théoriques Et Méthodologiques - Brany, F.K. (University of Ghana, 2017)
The use of Oral Expressions is a very important tool in the teaching and learning of a language. In a practical language class, it is through conversations that both the teacher and the student understand each other. Oral expression therefore facilitates one’s perfection of a language. We have observed that, most SHS graduates, obtained excellent grades (A1, B2 or B3) in the French language in their WASSCE examinations. But majority of these students, pursuing French at the tertiary institutions often find it very difficult to express themselves in the French language orally. If these students, after three years of learning French are doing excellently in written French, why do they perform poorly in oral French? This research work established that the teaching of French at the SHS level most often, neglects the oral activities of the syllabus that will balance the competences of the students. We selected two schools in Ho Municipality. With qualitative and quantitative methods and through observations, questionnaires and interviews, we collected our data. The results of our analyses revealed that teachers at the SHS often concentrate on the written competences of their students and examination candidates to the detriment of the oral aspects in their lesson planning and delivery. Moreover, most of their methods of teaching FLE classes are not activity oriented enough to compel the students to speak the language. Also the fact that English is used as the medium of instruction in most of the FLE classes already explains the poor performance of these students in oral French. We have also established that FLE Evaluation is mostly centred on written competences. This research therefore suggested some pedagogical steps that will help balance the development of equal competences of oral and written French in the teaching and learning of FLE.
Thesis (MPhil)
Keywords: Oral Expressions; Teaching; Learning